2012
DOI: 10.1093/carcin/bgs367
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cox-2 inhibitor celecoxib induces epithelial-mesenchymal transition in human lung cancer cells via activating MEK-ERK signaling

Abstract: Increasing evidence has suggested that high expression level of cyclooxygenase-2 (Cox-2) is associated with the malignancies of non-small cell lung cancer (NSCLC), leading to a rationale of applying Cox-2 inhibitors as adjuvant therapy in the treatment of NSCLC. However, the addition of celecoxib, a selective Cox-2 inhibitor, to chemotherapy in clinical trials failed to benefit the survival of NSCLC patients, which urges the investigation to re-evaluate this strategy for NSCLC treatment. In this study, we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 37 publications
2
46
1
Order By: Relevance
“…A certain portion of NSCLC patients can not benefit from NSAIDs, and they still suffer from rapid progression of tumor in clinical practice. Studies have confirmed that Celecoxib can promote epithelial-mesenchymal transition (EMT) of cancer cells, leading to increased metastatic risk [17]. Taken together, COX-2/HIF-1α signaling was probably not the only IL-1β downstream pathway to promote cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A certain portion of NSCLC patients can not benefit from NSAIDs, and they still suffer from rapid progression of tumor in clinical practice. Studies have confirmed that Celecoxib can promote epithelial-mesenchymal transition (EMT) of cancer cells, leading to increased metastatic risk [17]. Taken together, COX-2/HIF-1α signaling was probably not the only IL-1β downstream pathway to promote cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor tissues, DDR2 overexpression is often positively correlated with Vimentin and negatively with E-cadherin (19,20). DDR2 overexpression in tumor cells has previously been demonstrated to be sufficient in inducing morphological changes, and promoting enhanced migration and invasion, which are essential biological processes in tumor metastasis (23,25). The increased migration and invasion capacity are dependent on the secretion of matrix metalloproteinases (MMP) (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is hypothesized that, by inhibiting COX-2, the COX-1 pathway may become dominant in normal cells, thereby assisting tumor growth in COX-2-negative cells. Other investigators reported that celecoxib treatment induced epithelial-to-mesenchymal transition, which promoted cell invasion and rendered cells resistant to chemotherapy (28). These negative effects may obscure the positive effects in COX-2-expressing patients.…”
Section: Grade ------------------------------------------------------mentioning
confidence: 99%